2011
DOI: 10.1007/s10071-011-0420-7
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons discriminate between human feeders

Abstract: Considered as plague in many cities, pigeons in urban areas live close to human activities and exploit this proximity to find food which is often directly delivered by people. In this study, we explored the capacity of feral pigeons to take advantage of this human-based food resource and discriminate between friendly and hostile people. Our study was conducted in an urban park. Pigeons were fed by two experimenters of approximately the same age and skin colour but wearing coats of different colours. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…The ability to discriminate individual humans allows animals to direct appropriate behaviors towards specific individuals (Bee, 2006). For example, pigeons are capable of discriminating between friendly and hostile humans (Belguermi et al, 2011).…”
mentioning
confidence: 99%
“…The ability to discriminate individual humans allows animals to direct appropriate behaviors towards specific individuals (Bee, 2006). For example, pigeons are capable of discriminating between friendly and hostile humans (Belguermi et al, 2011).…”
mentioning
confidence: 99%
“…Dittrich et al, 2010;Belguermi et al, 2011) we did not artificially manufacture encounters with specific humans involving exclusively negative or positive events. In fact, two of the familiar humans captured, released and fed the birds on a regular basis, one was only involved in cleaning the aviaries and one was entering the aviaries but not handling the birds directly.…”
Section: Discussionmentioning
confidence: 99%
“…Marzluff et al, 2010). Dittrich et al (2010) emphasised the importance of human facial cues for discrimination whereas other studies indicated a facilitating effect of different clothing or acoustic cues on discrimination (Belguermi et al, 2011;Sliwa et al, 2011;Wascher et al, 2012). Consequently, the use of pictorial representations offers the opportunity to restrict and select all cues given during discrimination.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chickens ( Gallus gallus domesticus )19 and jungle crows ( Corvus macrorhynchos )23 can also discriminate pictures of human faces, and American crows ( Corvus brachyrhynchos ) recognize individual face masks worn by humans and respond to a particular mask regardless of the person wearing it22. This ability may be a result of pre-existing neural specializations as these species often live in urban habitats and interact with humans3031 as well as demonstrate conspecific recognition based on visual cues3233343536. We therefore wondered whether teleost fish, the earliest vertebrate taxon lacking neocortical circuitry and one that is unlikely to have evolved any specializations for discriminating human faces, would show similar human face discrimination abilities.…”
mentioning
confidence: 99%